Dilemas e contradições sobre a concepção de infância presente no Referencial Curricular Nacional da Educação Infantil - RCNEI - Andrade, Carla Lisbôa (2015)
This work is a study on the design of this childhood in the National Curriculum Reference for Early Childhood Education - RCNEI. In this sense, we tried to reflect on the educational policies geared for children 0-6 years old from 1960 to 1990, is characterized by childhood ways of seeing and conceiving it. To dye the objectives proposed herein, the methodology used was documentary and bibliographic character. Initially, it presents the trajectory of childhood concept in Brazilian educational policies, over time, especially about the looks attributed to childhood in RCNEI produced in 1998. In relation to educational proposals for children in the modern period, between the century XVI and XVII, the childhood understandings disseminated by Comenius, Rousseau, Pestalozzi and Froebel were examined. In the Brazilian educational policies, it was found that, until the 1980s, there was an intense concern for the biological aspect of the child related to hygiene, health and nutrition. Thus, there emerged a kind of care focused on children who were in unfavorable economic conditions in relation to social class and cultural environment to which they belonged. Pre-school educational policies portray the childhood concept route, for example, in the 1930s, when the hygienist ideology manifested itself in defense of the inspection body and the environment, as well as the care of children had these same precepts. From 1930 to 1980, the policy for children, educational character, privileged works of social assistance. The Federal Constitution of 1988 came to regard the child as a subject of rights, and the Statute of Children and Adolescents - ECA, in 1990, incorporated the doctrine of full protection, which meant giving priority to children and adolescents, as well as children were considered as citizens with all rights and how to be in development. The LDB No. 9394, 1996, reaffirmed the right to education guaranteed by the 1988 Constitution Already the Reference National Curriculum from Kindergarten - RCNEI can be considered as a document which is presented as an advancement of early childhood education, because tackle and overcome educational issues related to welfare tradition of creches and advance the teaching of preschools. It can also be understood as a curricular framework that gave conceptions and practices that are presented in their text in an attempt to overcome them, such as preschool be guided along the lines of elementary school.